Stability while walking is affected by walking speed and cognitive load - Mirmoezzi, Masoud; Namazizadeh, Mahdi; Sadeghi, Heydar; Mohammadi, Fariba (International archives of health sciences, 2019)
Aims: The aim of this study is to examine the effect of walking speed and cognitive load on learning gait stability in younger and older adults. Materials and Methods: Ten adults (five males and five females) and ten elderly (five males and five females) were healthy volunteers without a history of falls. He was asked to do three tasks on a treadmill with speed (preferred, fast, and slow) with/without cognitive load. The gait-stability ratio (GSR) for each of the above conditions was calculated in terms of both younger and older adults. Two-way repeated measures ANOVA was used to examine the mean differences at a significance level of 0.05. Results: The results showed that the cognitive performance score decreases with increasing speed. Moreover, at faster and slower speeds than prefer speed with/without cognitive load, GSR is higher, and this value was observed more in elderly than in adults (P < 0.05). Conclusion: The elderly, through different walking strategies, especially the lowering phase, provide more double support while walking, so that they will fall less with increasing steadiness.